Software based graphic signal calculator - Teo, Kai Yi (Nanyang Technological University, 2021)
Signals are widely used in engineering contexts, especially in Electronic and Electrical Engineering (EEE). Signals are functions that are able to contain and transfer information, whether it is the speech of a person or information about a system. In the current day and age, signals play a crucial role in allowing information to be transmitted, whether it is between two physically connected systems or between communication equipment across vast distances. Therefore, it comes as no surprise that a basic understanding of signals is required in EEE courses and even becomes a core concept should a student choose to specialise in data or processing related fields. Despite the nature of signals being rooted in rather common mathematical functions, these signals can become challenging to visualise and conceptualise once they start to be manipulated in more complicated ways such as modulation. This signal generator will allow users to visualise their selected signals in a graph format, as well demonstrate the process of sampling signals. This will expose users to field of engineering where signals are a core concept, which is Digital Signal Processing. This program was written in C Language.